Strategi Manejemen Sarana dan Prasarana dalam Peningkatan Sekolah Adiwiyata - Dian Fasihah Kumala Dewi; Abdullah Aminuddin Aziz (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aims to explore and analyze strategic management of facilities and infrastructure in strengthening the Adiwiyata School program at SMPN 1 Diwek through a qualitative case study approach. Data were collected using observation, interviews, and documentation, then analyzed using the Miles and Huberman model, including data collection, reduction, presentation, and conclusion drawing, with data validity ensured through source and technique triangulation. The findings show that the management of facilities and infrastructure is implemented through systematic functions of planning, organizing, implementing, and controlling, which effectively support the success of the Adiwiyata program. This strategy has contributed to the creation of a clean, green, healthy, and comfortable school environment while also increasing the active participation of school members in environmental activities. Overall, the study emphasizes that well-managed facilities and infrastructure play a crucial and persuasive role in sustaining and improving the quality and continuity of the Adiwiyata School program.